1996
DOI: 10.1007/bf02318961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of local plant growth conditions on non-fastidious bacterial contamination of meristem-tips ofHydrangea culturedin vitro

Abstract: A high incidence of in vitro bacterial contamination (69%) has been detected in meristem-tip explants of Hydrangea from widely differing locations in Ireland and the UK. The bacteria were characterised by API 20E biochemical test kits and by fatty acid profile analysis. The results obtained from the different methods were compatible and anomalies were explicable in terms of the limitations of the respective methods. The majority of the isolates were environmental or animal-associated bacteria with clusters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…2), exist near hydrangea SAMs. Cassells and Tahmatsidou (1996) studied bacteria on shoot tips obtained from 71 individuals of 19 hydrangea species collected in Ireland. They concluded that the origin of explants determines the bacterial flora on the shoot tips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), exist near hydrangea SAMs. Cassells and Tahmatsidou (1996) studied bacteria on shoot tips obtained from 71 individuals of 19 hydrangea species collected in Ireland. They concluded that the origin of explants determines the bacterial flora on the shoot tips.…”
Section: Discussionmentioning
confidence: 99%
“…explants are cultured in vitro, microbial contamination frequently occurs (Cassells and Tahmatsidou, 1996). In the case of shoot tip or node culture, almost all explants are contaminated with a white, pink or yellow bacterial colony ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Conforme Bergey's Manual of Systematic Bacteriology (Krieg & Holt, 1984). se num dos mais importantes e tem sido relatado por diferentes autores como um dos principais contaminantes na cultura de tecidos (Leifert et al, 1989;Cassells & Tahmatsidou, 1996;. Embora não tenham sido realizados testes mais específicos para comprovar tal hipótese, é provável que as estirpes isoladas B2 e B7A, classificadas como da família Enterobacteriaceae, pertençam a este gênero.…”
Section: Resultsunclassified
“…These microorganisms are introduced into in vitro cultures via explants Waites 1990, 1994), air or humans (Leifert et al 1989;Leifert and Cassells 2001). Endophytic bacteria have been reported to live in protoplast cultures of Discorea (Mantell 1997(Mantell , 1998, callus cultures of Phoenix dactylifera (Leary et al 1986), garlic (Fellner et al 1996), Norway spruce (Ewald et al 2000), Pyrethrum (Bergant et al 2005), embryogenic cultures of Norway spruce (Ewald et al 1997), meristem-tip cultures of Hydrangea (Cassells and Tahmatsidou 1996), shoot cultures of birch (Gordon and Brown 1988), Cynara scolymus (Peńalver et al 1994), mint (Reed et al 1995), Robinia pseudoacacia , Echinacea (Lata et al 2006), papaya (Thomas et al 2007a, b) and in leaves and roots of Zantedeschia aethiopica plantlets (Gunson 1992) and of Vitis vinifera (Thomas and Prakash 2004) under in vitro conditions. Endophytic fungi were found in roots and leaves of micropropagated plants from Bouteloua eriopoda and Atriplex canescens (Barrow et al 2004), in shoot tip cultures of pejibaye (de Almeida et al 2005), apple (Kolozsvári-Nagy et al 2005) and in suspension cell cultures of B. eriopoda (Lucero et al 2008).…”
Section: Introductionmentioning
confidence: 98%